The practice of judicial review in China - Zhai, Guoqiang (2013)
The author classifies constitutional control models in the world inthree groups: Constitutional Court model, judicial revision and parliamentary control. China’s model is the last one. Then, underlines, two main goals of constitutional control: human rights protection and constitutional control of the legal system. Finally, suggests a debate about which body should bein charge of the constitutional control, whether that important work shall continue under the National People’s Congress, become a non legislative body or if it shall stay in charge of China’s Superior Court.